2012
DOI: 10.1038/emboj.2012.273
|View full text |Cite
|
Sign up to set email alerts
|

ROS-mediated vascular homeostatic control of root-to-shoot soil Na delivery inArabidopsis

Abstract: Sodium (Na) is ubiquitous in soils, and is transported to plant shoots via transpiration through xylem elements in the vascular tissue. However, excess Na is damaging. Accordingly, control of xylem-sap Na concentration is important for maintenance of shoot Na homeostasis, especially under Na stress conditions. Here we report that shoot Na homeostasis of Arabidopsis thaliana plants grown in saline soils is conferred by reactive oxygen species (ROS) regulation of xylem-sap Na concentrations. We show that lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(77 citation statements)
references
References 59 publications
(117 reference statements)
1
75
0
Order By: Relevance
“…The transcription factors that control enhanced AtHKT1;1 expression have yet to be determined. A genetic screen for soil salinity-sensitive ( sss ) mutants led to the isolation of the sss1-1 mutant, which showed strong Na + hypersensitivity in shoots [93]. The SSS1 locus encodes the AtrbohF protein, an NADPH oxidase catalyzing ROS production [93].…”
Section: Hkt As Major Player In Plant Salt Tolerance and Root-to-shoomentioning
confidence: 99%
See 2 more Smart Citations
“…The transcription factors that control enhanced AtHKT1;1 expression have yet to be determined. A genetic screen for soil salinity-sensitive ( sss ) mutants led to the isolation of the sss1-1 mutant, which showed strong Na + hypersensitivity in shoots [93]. The SSS1 locus encodes the AtrbohF protein, an NADPH oxidase catalyzing ROS production [93].…”
Section: Hkt As Major Player In Plant Salt Tolerance and Root-to-shoomentioning
confidence: 99%
“…A genetic screen for soil salinity-sensitive ( sss ) mutants led to the isolation of the sss1-1 mutant, which showed strong Na + hypersensitivity in shoots [93]. The SSS1 locus encodes the AtrbohF protein, an NADPH oxidase catalyzing ROS production [93]. Interestingly, the lack of AtrbohF in root pericycle and vascular parenchyma cells abolished salinity-induced ROS accumulation in the vasculature and caused Na + over-accumulation in shoots with increased Na + levels in xylem sap [93].…”
Section: Hkt As Major Player In Plant Salt Tolerance and Root-to-shoomentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its charge, this short-lived ROS is unable to passively cross the lipid bilayer and remains in the apoplast, where it is rapidly converted into another species, H 2 O 2 , either spontaneously or in a reaction catalyzed by the superoxide dismutase (SOD; Browning et al, 2012). The functions of plant NADPH oxidases stretch beyond stress responses and include roles in development (Sagi and Fluhr, 2006; Takeda et al, 2008), in sodium transport in the xylem sap (Jiang et al, 2012), and intriguingly also in long-distance (“systemic”) ROS signaling (Miller et al, 2009). In Arabidopsis wounding, heat stress, high light, and increased salinity result in RbohD-dependent systemic spread of the oxidative burst along the rosette leaves.…”
Section: Ros In the Apoplastmentioning
confidence: 99%
“…A study with the Arabidopsis mutant atrbohF ( Arabidopsis thaliana respiratory burst oxidase protein F), showed that AtRbohF increases root vascular ROS levels in response to salinity, thereby reducing the amount of Na + in the xylem and, consequently, the amount of Na + exported to the shoots [78]. One hypothesis to explain the effect of AtRbohF on xylem Na + levels is that ROS stimulates AtHKT1;1 expression or activity, because AtHKT1;1 is involved in Na + unloading from the xylem (Figure 1) [6,12,19,21,49].…”
Section: Hkt Regulationmentioning
confidence: 99%